ANALYSIS OF NUMERACY SKILLS IN GRADE VI ELEMENTARY SCHOOL STUDENTS IN SOLVING MINIMUM COMPETENCY ASSESSMENT QUESTIONS - Astriani, Linda; Akyuni, Nurul Izzah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This piece of writing is inspired by the inadequate numeracy skills of students, leading to their confusion when it comes to creating visual representations and comprehending the analysis related to the problems they are tasked with. The minimum competency assessment serves as a tool to evaluate students' numeracy skills and, in turn, enhances the overall quality of elementary education. The primary objective of this study was to elucidate the numeracy skills of students and to delve into their responses when addressing questions in the minimum competency assessment. For this research, a descriptive qualitative method with a case study approach was employed. The research subjects comprised sixth-grade students at Pondok Cabe Ilir 01 State Elementary School during the odd semester of the 2023/2024 academic year. Data collection methods encompassed observation, numeracy minimum competency assessment tests, interviews, documentation, and data triangulation. Data analysis involved data reduction, data presentation, and drawing conclusions.The findings of this research revealed that students' numeracy skills fell into three categories: high, medium, and low, based on their performance across three specific indicators. The implications of this study are significant for schools, educators, and students, as they provide valuable insights into the preparation and enhancement of numeracy skills when addressing questions in the minimum competency assessment.